Peningkatan Jalan Menggunakan Perkerasan Kaku (Rigid Pavement) pada Ruas Jalan Letnan Sukarna Kecamatan Ciampea Kabupaten Bogor - Winara, Agriatama Hegar; Rulhendri, Rulhendri; Alimuddin, Alimuddin; Lutfi, Muhamad (Universitas Ibn Khaldun, 2023)
ABSTRACT: Road is the main land transportation infrastructure to move from one place to another places for every traffic user who passes through it, so the volume of vehicles on these roads must be able to be supported by adequate road pavement. Letnan Sukarna road is the connecting access for Rancabungur and Ciampea sub-districts. The existing condition of the road is in the form of Flexible Pavement, however there are several points that can be categorized as moderate to heavily damaged roads. The damage is in the form of longitudinal cracking and potholes that is caused by excessive vehicle loads, malfunctioning of drainage channels and high rainfall. In this study, a comparison of rigid pavement calculations uses the 1993 AASHTO and Bina Marga 2003 methods on Letnan Sukarna Road, Ciampea District, Bogor Regency. This study aims to obtain data on existing conditions and to find out the comparison of rigid pavement thickness. From the calculation results of the AASHTO 1993 method, the thickness of the pavement is 20 cm with transverse connections using dowels with a diameter of 13 mm, length 635 mm, a distance of 1117 mm, a longitudinal connection using a tie bar with a diameter of 25 mm, a length of 450 mm and a distance of 300 mm. Whereas with the Bina Marga 2003 Method, that is obtained a thickness of 18 cm with a transverse connection using a dowel with a diameter of 25 mm, length of 450 mm, a distance of 300 mm, a longitudinal connection using a tie bar with a diameter of 16 mm, a length of 750 mm and a distance of 700 mm. The difference in pavement thickness is quite small, namely 2 cm. It is influenced by differences in the input parameters of the two methods.